GESTÃO DE PROCESSOS EM UMA UNIDADE DE TRATAMENTO INTENSIVO: UM ESTUDO DE CASO - Valle, Luis de Almeida (2013)
Process Improvement methodologies were applied to a hospital intensive care unit (ICU) in the present study, with the aim of covering existing gaps in the health management, and thus obtaining improvements in the quality of the services rendered. For this purpose, the Process Management approach was employed, seeking the Improvement of the Work Processes related to ventilator-associated pneumonia (VAP). In order to gather and analyze the required data, techniques and tools for the improvement and change of organizational processes were used, and semi-structured questionnaires were applied. In the ICU where this Case Study was developed, no evidences of standardized protocols for the prevention, diagnosis and treatment of VAP were found. However, as a positive factor, the commitment of the sector s professionals to performing routines and to teamwork was confirmed, and a favorable and friendly environment for the implementation of protocols for VAP was also confirmed. The results enabled the construction of protocols for preventing, diagnosing and treating VAP in the said hospital unit, for which the data and analysis of the case were taken into consideration, as well as Brazilian and international protocols from acknowledged institutions.